Continuous Infusion Ketorolac for Postoperative Analgesia Following Unilateral Total Knee Arthroplasty. (June 2017) - Schwinghammer, Amy J.; Isaacs, Alex N.; Benner, Rodney W.; Freeman, Heather; O'Sullivan, Jacob A.; Nisly, Sarah A.
Background: Previous clinical trials have demonstrated benefit with the addition of continuous infusion (CI) ketorolac to a multimodal pain regimen in surgical patients. Data following major orthopedic surgery are minimal and conflicting.Objectives: To evaluate CI ketorolac use following unilateral total knee arthroplasty (TKA) through assessment of patient-reported pain scores, opioid consumption, and safety outcomes.Methods: This was a retrospective, open-label cohort study that included patients undergoing unilateral TKA at a single-center teaching hospital. Participants were categorized into 2 study groups based on postoperative management: CI ketorolac or opioid protocol (OP). The first group received a ketorolac 30-mg bolus followed by CI 3.6 mg/h plus as-needed (PRN) opioids. The OP group received PRN narcotics in a tiered protocol. The primary end point was comparison of median pain scores. Secondary end points included opioid consumption (morphine equivalent units [MEUs]) in the first 48 hours postoperatively, length of stay, and adverse effects.Results: Of 447 patients screened, 191 were analyzed (CI ketorolac, n = 116; OP, n = 75). Median pain scores were significantly lower in the CI ketorolac group at 48 hours postoperatively (3 [2-4] vs 3.5 [2.5-5], P = 0.033). Cumulative MEUs at 48 hours were significantly lower in the CI ketorolac group (33.9 ± 38.5 mg vs 301.6 ± 36.6 mg, P < 0.001). Patients in the CI ketorolac group experienced less respiratory depression (5.2% vs 25.3%, P < 0.001) and less naloxone administration (0% vs 8%, P = 0.002) compared with the OP group. Other adverse effects were similar among groups.Conclusions: Postoperative CI ketorolac improved pain control while reducing opioid consumption and adverse effects.